HUBUNGAN TOLERANSI STRES, SHIFT KERJA DAN STATUS GIZI DENGAN KELELAHAN PADA PERAWAT IGD DAN ICU (STUDI DI RSI SULTAN AGUNG SEMARANG) - Saadatul Maghfiroh; Mifbakhuddin M (Universitas Muhammadiyah Semarang, 2015)
Background: Mental and physical workload occurred in the ER and ICU Nurses was so high, thus allowing nurses were stress occurs. It was going to effect in healthy so that they got exhauted. besides stress, shiftwork and nutrition status can also causes fatigue. The aim of this research was to know the correlation between tolerance of stress, shiftwork and nutrition status with fatigue. Method: The research was an analytic with approach retrieval datain cross-sectionaltechnique.The study was conducted in RSI Sultan Agung Semarang with 44 population and 34 sample was consist of 17 ER nurse and 17 ICU nurse, and the technique with purporsive sampling.The variable in this resecrhinclude the independent variablesthat was tolerance of stres, workshift dan nutrition status.denpendent variable that was fatigue and disturber variable that was history of sick. hypothesis test with person product moment, rank-spearmen and chi-square. Result: (a) the majority of Nurses has good tolerance of stress within the percentage 79,4%; (b) the Nurses on afternoon shiftwork has the highest percentage that was 35,3%; (c) 61,8% of Nurses has normal nutrition;(d) the Nurses being mild fatigueon highest percentagethat was 64,7%; (e) there did not corelation between tolerance of stres with fatigue; (f) there did not corelation between work shift with fatigue; (g) there did not corelation between nutrition status with fatigue. Conclusion: there did not corelation between tolerance of stress, work shift and nutrition status with fatigue on nurse in ER and ICU.